2017
DOI: 10.1158/1078-0432.ccr-17-0821
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Heterogeneity in APC and KRAS Arises at the Crypt Level and Leads to Polyclonality in Early Colorectal Tumorigenesis

Abstract: Purpose The majority of genomic alterations causing intratumoral heterogeneity (ITH) in colorectal cancer (CRC) are thought to arise during early stages of carcinogenesis as a burst but only after truncal mutations in APC have expanded a single founder clone. We have investigated if the initial source of ITH is consequent to multiple independent lineages derived from different crypts harboring distinct truncal APC and driver KRAS mutations, thus challenging the prevailing monoclonal monocryptal model. Experi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 36 publications
(44 reference statements)
2
24
0
Order By: Relevance
“…In addition to somatic mutations, Car R3 also had distinct CNAs and loss of heterogeneity mutations compared with the other three regions (figure 2D and online supplementary figure 9B,C). 29 Clonal architecture analysis of other multiregionally sampled lesions from FAP4 and FAP5 supported the punctuated evolution model; most of the potential driver mutations and recurrent CNAs were clonal (online supplementary figures 6 and 7). 30…”
Section: Clonal Architecture Of Lesions At Different Evolutionary Stamentioning
confidence: 61%
See 1 more Smart Citation
“…In addition to somatic mutations, Car R3 also had distinct CNAs and loss of heterogeneity mutations compared with the other three regions (figure 2D and online supplementary figure 9B,C). 29 Clonal architecture analysis of other multiregionally sampled lesions from FAP4 and FAP5 supported the punctuated evolution model; most of the potential driver mutations and recurrent CNAs were clonal (online supplementary figures 6 and 7). 30…”
Section: Clonal Architecture Of Lesions At Different Evolutionary Stamentioning
confidence: 61%
“…52 Gausachs et al also reported the possibility of a 'genetic field effect' in patients with FAP based on finding that physically separated crypts share hotspot mutations in KRAS. 29 However, the inference of the evolutionary relationship based on several mutation sites limits the reliability of this conclusion. Our analysis based on WES further confirmed the theory of field cancerisation in patients with FAP.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in this study, it was also observed that the at-risk colon mucosa in part displayed the genetic alterations observed in adenomas, thus indicating the evolution from normal tissue to premalignant adenoma and surrounding mucosa and then to carcinoma [ 218 ]. Gausachs et al, in a recent study, provided evidence that the mutational heterogeneity in APC and KRAS observed in adenomas arises at the crypt level [ 220 ]. This conclusion was based on the ultrasensitive genotyping of matched bulk biopsies and individual crypts of colorectal adenomas and carcinomas: this analysis observed the presence of novel APC mutations, abundant wild-type APC crypts coexisting with mutant crypts, and mutational heterogeneity in KRAS within crypts, events not detectable through the analysis of standard biopsies [ 220 ].…”
Section: Somatic Genetic Abnormalities In Colon Cancermentioning
confidence: 99%
“…22 Multiple trunk APC mutations and heterogeneity of KRAS mutations were also found in early colorectal adenomas, suggesting that ITH is already present in such lesions. 23 The early evolutionary progress of CRC is branched, while most mutations in advanced CRC are neutral. Time is a natural process that enables the expansion of the early selection effect.…”
Section: Evolutionary Pathway Of Crcmentioning
confidence: 99%